EQUALITY BEFORE THE LAW IN REGIONAL HEAD ELECTION TRIALS - Firdiansyah Putra, M. Farrel; Sujatnika, Ghunarsa (Universitas Lampung, 2024)
General elections and regional head elections are vital expressions of popular sovereignty and democratic representation within the framework of the rule of law. These elections underscore that sovereignty and power reside with the people. However, the electoral process often leads to disputes, which can arise from administrative issues, criminal activities, and the results of vote counting. Consequently, an effective election dispute resolution mechanism is essential, emphasizing the principle of equality before the law for all parties involved, to ensure the integrity of the electoral process. This research employs normative methods to examine the laws and regulations governing regional head elections. It analyzes relevant data and case examples in relation to the principle of equality before the law in both legislative and regional head elections. The novelty of this research lies in its exploration of the equal standing of parties before the law, particularly in the context of disputes arising during regional head elections.